IMPLEMENTASI PEMBELAJARAN BERBASIS PROYEK DIGITAL DALAM MATA KULIAH PENGANTAR STUDI ISLAM UNTUK MENINGKATKAN LITERASI KEISLAMAN MAHASISWA PROGRAM STUDI PIAUD UIN SUNAN KALIJAGA - Nelly Setia Wati; Muhammad Wasith Achadi; Rohinah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the low level of student engagement in contextual and creative Islamic learning in the digital era. The purpose of this research is to analyze the implementation of Digital Project Based Learning (DPjBL) in the Introduction to Islamic Studies course and its contribution to improving Islamic literacy among students of the Early Childhood Islamic Education Department at UIN Sunan Kalijaga Yogyakarta. This research employed a descriptive qualitative method with a case study approach through observation, interviews, and documentation. The results show that DPjBL encouraged students to produce various digital products such as videos, podcasts, and infographics that represent Islamic values in a contextual and moderate way. The project also enhanced students’ critical thinking, collaboration, and ethical awareness in digital da’wah. The study concludes that DPjBL effectively integrates Islamic values with digital technology and is recommended for broader implementation in Islamic education courses to strengthen 21st-century competencies.